“GIVE VATICAN II A CHANCE” Sebuah Renungan Pribadi Mengenai Masa Depan Hubungan Oikumenis Protestan-Katolik di Indonesia - Emanuel Gerrit Singgih (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2013)
Experience of encountering and being together with friends of a number of other religious traditions has contributed to changing the way one thinks, speaks and acts. This occurs only when there is a sincere readiness to open oneself to the other while at the same time acknowledging and appreciating plurality in the human family. In the Christian Church, both Catholic and Protestant, this can be understood as a result of the Second Vatican Council. In the context of Indonesia, and more specifically in Jogyakarta and in NTT Province, ecumenical relations between Catholics and Protestants indicate a desire for renewal (aggiornamento) in our common life. This is clear in collaboration between institutes of higher education, such as studying theology together, the use of a common Bible, acceptance of the deuterokanonika, meditation in common, and so forth. In such togetherness the ecclesial unity that Jesus prayed for derives its meaning. Kata-kata kunci: Perjumpaan, pembaruan, kesatuan, oikumene, tantangan, misi, kontekstualisasi, persaudaraan sejati